Best Answer

7x - 5 = -13 + 56

Perform the indicated addition on the right side of the equation:

7x - 5 = 43

Add 5 to each side:

7x = 48

Divide each side by 7 :

x = 48/7 = 6 6/7

Q: How do you solve 7x - 5 equals -13 plus 56?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

309?

56 plus 1 equals 57. == ==

1 + 2 + 56 = 59

56 multiplied by 13 equals 728. the result is 728.

First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .

Related questions

a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28

Set up the equation and solve for z: 28 + z = 56 (next, subtract 28 from each side of the equaition to solve) z = 28

309?

112

512 + 13 + 56 + 2124 = 2705

56 plus zero

x - 56 = 79 x - 56 + 56 = 79 + 56 x = 135

56 plus 1 equals 57. == ==

1 + 2 + 56 = 59

56 multiplied by 13 equals 728. the result is 728.

First, subtract 3x from each side of the equation. Then, divide each side of the equation by 7 .

13/56 + 40/56 = 53/56